PENGEMBANGAN SUMBER DAYA MANUSIA PT TELEKOMUNIKASI INDONESIA DALAM MENINGKATKAN KINERJA PERUSAHAAN MENGHADAPI ERA PERSAINGAN BEBAS - Ansen, Yopines (2011)
The main problem at Indonesia Stated-Owned Telecommunication Company Inc., Office of Bandung Regional Telecommunication Service, in facing a tough competition is the poor performance of both individual and the company. This poor performance is caused by various factors including work environment, leadership, work motivation, business culture, work satisfaction, and knowledge, skill and attitude development. To improve the performance, a study investigating the factors above is necessary. The design used in this study is "Causal Design" involving 297 staff as sample, which is derived from 1295 staff as the population with the probability level of 5%. The data are collected through interview, questionnaire, observation, and library research. The data are analysed using Path and Factor Analyses. The type of the questionnaire used is the one of Likert Scale type. Conclusions : First, the company should welcome the change and develop strategies in accordance with the change of business environment. Second, competency based staff development will make them capable of implementing duties and jobs in accordance with the assigned work standard. Third, the management should become the role model in attitude and action. Fourth, the company should pay its attention to the consumer wants and needs. Fifth, the staff should have motivation and sense of belonging. Sixth, the company should provide recognition and reward for achievement acquired. Seventh, the management should give direction in achieving the goal of the company. Eight, a good work environment will influence optimum achievement. Ninth, the involvement of the staff in decision-making will result in improved sense of belonging. Tenth, the sustainable quality improvement plays a very significant role. Eleventh, the influence of work potency, work hope, attitude development, work ability, and work environment towards individual work performance is 35,20%. Twelfth, the influence of work potency variable, attitude development, work ability, and work environment towards company performance is 61,60%. Thirteenth, the influence of individual performance variable towards company performance is 32,79%. Recommendations : Firstly, it is suggested that to improve the ability of the staff highest level possible, human resource development through sustainable education and training be necessary. Secondly, there should be a high commitment of the company management towards the success of the human resource development. Thirdly, the company should be able to provide the best service to the customers so that they become loyal customers. Fourthly, Total Quality Management should be applied in managing the company. Fifthly, the company should possess the certificate of ISO 9000 Series. Sixth, work culture should be implemented. Seventh, education and training should be carried out through " strategic learning plan" approach. Eight, it is necessary to adopt competency based approach to human resource development. Ninth, the work health and safety program should be implemented. Tenth, it is necessary that the efficiency and effectiveness of education and training be improved through distance learning, multimedia application and module system.